2013
DOI: 10.1017/s1352465813000167
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Functioning in Individuals at Clinical High Risk for Psychosis

Abstract: A poorer performance in metacognition can be seen as a marker of developing a full blown psychotic illness and confirms the potential value of assessing metacognitive beliefs in individuals vulnerable for psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
(24 reference statements)
3
38
0
1
Order By: Relevance
“…Finally, this view is supported by 3 recent studies suggesting that metacognitive beliefs (Barbato et al, 2014;Brett, Johns, Peters, & McGuire, 2009) and deficits (Scheyer, Reznik, Apter, Seidman, & Koren, 2014) are prevalent among people with attenuated psychosis syndrome (APS), and have some level of sensitivity in predicting the development of psychosis among this population (Barbato et al, 2014).…”
Section: Metacognition As a Possible Correlate Of Sdmentioning
confidence: 91%
“…Finally, this view is supported by 3 recent studies suggesting that metacognitive beliefs (Barbato et al, 2014;Brett, Johns, Peters, & McGuire, 2009) and deficits (Scheyer, Reznik, Apter, Seidman, & Koren, 2014) are prevalent among people with attenuated psychosis syndrome (APS), and have some level of sensitivity in predicting the development of psychosis among this population (Barbato et al, 2014).…”
Section: Metacognition As a Possible Correlate Of Sdmentioning
confidence: 91%
“…Research using samples of people at risk of developing psychosis suggests that at risk mental state (Morrison et al, 2006) and subsequent transition to first episode psychosis (Barbato et al, 2013;Morrison, Bentall, et al, 2002) is associated with a greater endorsement of negative metacognitive beliefs. A higher number of negative beliefs has also been related to increased distress (Barbato et al, 2013;Brett, Johns, Peters, & McGuire, 2009;Oosterhout, Krabbendam, Smeets, & van der Gaag, 2013) and a more severe and chronic course of illness (Austin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The scale is designed under the theoretical notion that meta-cognitive beliefs guide ones thinking and coping styles, and those maladaptive meta-cognitions contribute to the maintenance of psychological disorders. MCQ based studies have demonstrated that relative to healthy people, CHR samples endorse high negative beliefs in general (Morrison et al, 2006;Brett et al, 2009;Barbato et al, 2013;Welsh et al, 2013), high negative beliefs about uncontrollability of thoughts and corresponding danger (Morrison et al, 2006;Brett et al, 2009;Barbato et al, 2013), low confidence in the efficiency of their cognitive skills (Morrison et al, 2006;Brett et al, 2009) and diminished cognitive self-consciousness (Morrison et al, 2006;Brett et al, 2009;Welsh et al, 2013). There is also some recent evidence that meta-cognitive abilities in CHR may predict transition to psychosis in CHR youth (Barbato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important, as people at CHR of psychosis show impaired meta-cognitive abilities relative to healthy controls (Barbato et al, 2013) and decreased gray matter volumes in a number of regions implicated in the pathogenesis of psychosis (Fornito et al, 2008;Witthaus et al, 2010;Wood et al, 2010;Mechelli et al, 2011). In particular, the inferior and middle frontal cortices, anterior cingulate cortex, superior temporal cortex and insula appear to be the most affected cortical loci in first-and multi-episode schizophrenia (EllisonWright et al, 2008;Bora et al, 2011;Olabi et al, 2011;Radua et al, 2012;Fusar-Poli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%